Pendidikan Kesehatan Rebusan Daun Sirsak Terhadap Penderita Hipertensi di Panti Sosial Lanjut Usia Harapan Kita - Saputra, Andre Utama; Mardiono, Sasono (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Hypertension is a condition where a person experiences an abnormal increase in blood pressure in systole and diastole. There are many different ways to lower blood pressure, one of which is boiled water from soursop leaves. The aim of this community service is to determine the health education of soursop leaf decoction on reducing blood pressure in hypertension sufferers in the Harapan Kita nursing home in the city of Palembang. This Community Service uses a one group pre-test post-test design. Participants in this community service were 33 people suffering from hypertension in the Harapan Kita nursing home in the city of Palembang. With purposive sampling technique. This Community Service is carried out during the day by giving boiled water from soursop leaves twice. The data analysis used is the Paired Sample T test. The instruments in this study used SOP (standard operating procedure), blood pressure measurement observation sheet, Sphygmomanometer, and stethoscope. The results of this Community Service show that giving boiled water from soursop leaves has an effect on systolic blood pressure values with a P-Value = 0.000 and a diastolic blood pressure value P-Value = 0.001 so it can be concluded that there is an effect of boiled water on soursop leaves on reducing blood pressure in the elderly hypertension sufferers. The results of this Community Service show that boiled water from soursop leaves can reduce blood pressure in hypertension sufferers. Because of the antioxidant content, potassium ions, which can lower blood pressure in soursop leaves